(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The pending cases problem, which accounts for almost three crore cases, is one of the mosthorrific aspects of the Indian justice system.. Legislators introduced plea bargaining as a new way toreduce the number of cases that are pending. One of the most recent modifications to the criminal code,the Criminal Law Amendment Act, 2005, took effect in 2006 and made plea bargaining possible. About 10years have passed since the notion was first recognised in Indian criminal law. The goal of this article is toevaluate the concept’s success in India, taking into consideration the statutes and court rulings about it.Because of its pioneer role in plea bargaining, this essay is going to take a closer look at it. Additionally,the paper will compare both American as well as Indian versions of plea bargaining in order to highlightthe advantages and disadvantages of each method. An overview of the American style of pleabargaining, which has shown to be a highly effective strategy, will be provided in this article. Accordingto the introduction, the article’s main purpose is to examine the Indian model of plea bargaining in lightof the highly effective American approach. Plea bargaining in Indian courts might benefit greatly fromthe work done here, which could be put to good use.